Multidrug therapy for muscular dystrophy in a GRMD (Golden Retriever muscular dystrophy) model - Fernandes, Renata A.; Fratini, Paula; Nogueira, José L.; Abreu, Dilayla K.; Feder, David; Carreira, Ana Claudia O.; Miglino, Maria A. (Brazilian Journal of Veterinary Pathology, 2016)
Golden Retriever muscular dystrophy (GRMD) is a degenerative, progressive and lethal genetic disease, homologous to human Duchenne muscular dystrophy (DMD). For both there is no cure and clinical interventions are limited to treating clinical signs. As potential treatment, we did a pilot study in GRMD and administered a cocktail of frequently used drugs that might work synergistically. Biochemical blood values were investigated and histology and real-time PCR of muscle biopsies were performed. Significant improvements occurred in experimental Golden Retrievers dogs in regard to the levels of alanine aminotransferase, neutrophils, lymphocytes and CK, which began to show values closer to normal ones when compared to control animals, as well as moderate inflammatory infiltrates in the musculature, according to histology. The drug cocktail seemed to work systemically, but did not interfere with the gene defect, thus having potential value for maintaining the health status and preventing the progression of muscular dystrophy in GRMD model.